Organizational effectiveness through transformational leadership and technology innovation: a systematic literature review and future research agenda - Ahmad, Sajjad; Ali, Noor Azman; Jantan, Amer Hamzah; Bowyer, Dorothea; Campbell, Nadine; Md Reaz (Research Publishing Academy, 2020)
Taking an upper echelon theoretical perspective in public sector higher education, this systematic literature review had quadruple objectives. First, to identify the gap in the existing literature on transformational leadership (TL). Second, to suggest a comprehensive instrument for a higher-order construct of TL. Third, to propose a rigorous research framework for future empirical research, and fourth, to propose an appropriate research methodology for that empirical research. Using a systematic literature review approach, various databases were accessed to obtain current literature on the topic. Transformational leadership constructs were extensively explored for current concept developments and available measurement scales. A research model was proposed according to transformational leadership, and upper echelon theoretical frames and appropriate research methodology was recommended. The study found that the research on the TL, its antecedents, factors, and outcomes were still being developed. Various dimensions with different conflicting and complementing questionnaires and numerous instruments from the literature on TL construct have been identified. As a result, a research framework was proposed to conduct future research on transformational leadership and organisational effectiveness with a mediating role of technology innovation to fill the acknowledged gap. This study is among the first research to propose technology innovation in higher education context. Two of the newly launched techniques IPMA and CTA are recommended to enhance the robustness of any study involving technology innovation.